The Correlation Between Fear of Missing Out (FoMO) and Internet Addiction in Vocational High School Students - Setyaningsih, Nur; Widodo Sarjana; Natalia Dewi Wardani (Jurnal Psikiatri Surabaya, 2023)
Abstracts Background: Advanced and rapid technologic development has a great impact on the Indonesian education system. Indonesia was the sixth-largest internet users in the world. The increasing number of internet users potentially may increase the number of internet addicts caused by many factors, such as fear of missing out (FoMO). Objective: To determine the correlation between FoMO and internet addiction cases in Mitra Karya Mandiri Vocational High School, Brebes. Methods: This was a quantitative study with a cross-sectional design. Subjects of this study were all 11th-grade students of Mitra Karya Mandiri Vocational High School selected using a stratified random sampling method. The instruments used in this study was the Indonesian version of the sociodemographic questionnaire, the Internet Addiction Diagnostic questionnaire (KDAI) and the Fear of Missing Out questionnaire (FoMO-scale). Results: Most subjects (68.9%) did not have an internet addiction. There was a significant correlation between internet addiction with FoMO (p=0.009). The result of the ANOVA test showed that there were no significant differences in internet addiction from three majors of Mitra Karya Mandiri Vocational High School (p=0.586) and FoMO from three majors of Mitra Karya Mandiri Vocational High School (p=0.969). Conclusion: There was a significant correlation between internet addiction and FoMO. There was a significant correlation between internet addiction with gender and peer environment. However, there were no significant differences found between internet addiction and FoMO from each major.